DOMINANT FACTORS CAUSES OF DRUG ABUSE IN ADOLESCENTS AT THE LAMONGAN DISTRICT PENITENTIARY - Umam, Khotibul; Prasetyo, Agung (Journal of Vocational Nursing, 2020)
Introduction: The use of illegal drugs is increasing in adolescents and the consequences that will damage the generation so that it must be sought or known influencing factors as preliminary data in determining intervention. According to a preliminary survey at the Lamongan District Penitentiary in 2011, the number of suspects and defendants of drug abuse was 115 people, of whom 63 were teenagers. This study aims to determine the dominant factors that influence drug use in adolescents. Methods: The research design used in this study study uses a descriptive method, namely describing or explaining the factors that cause drug abuse in adolescents. The population in this study were all adolescent drug users in the Lamongan District Correctional Institution in May 2012 as many as 63 people. In this study the sampling technique used was purposive sampling, namely the technique of determining the sample by selecting samples among the population according to what the researcher wanted. In this study the instrument used was a closed questionnaire sheet. Data processing and data analysis by editing, coding, scoring, tabulating and analyzed purposively. Results: Based on the study, several factors were found to be the causes of drug users in adolescents at the Lamongan Penitentiary, including: Social environment (23%), personality (20%), family (8%), education (21%), and presence Drug (19%). Conclusion: Social environmental factors are the dominant factor causing drug abuse in adolescents at the Lamongan Penitentiary.